1998
DOI: 10.1063/1.122115
|View full text |Cite
|
Sign up to set email alerts
|

Infrared analysis of deuterated carbon–nitrogen films obtained by dual-ion-beam-assisted-deposition

Abstract: Articles you may be interested inThe effect of nitrogen incorporation on the bonding structure of hydrogenated carbon nitride films Structure and properties of carbon nitride thin films synthesized by nitrogen-ion-beam-assisted pulsed laser ablation J.Effect of temperature on carbon nitride films synthesized by ion-beam-assisted pulsed laser deposition Effects of increasing nitrogen concentration on the structure of carbon nitride films deposited by ion beam assisted deposition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 17 publications
1
24
0
2
Order By: Relevance
“…It is known that all the features in the 1000-1700 cm -1 region in carbon samples are due to skeletal C=C vibrations and this suggests that the 1000-1700 cm -1 band in this study is attributed to C=C modes or mixed C=N modes. 2,9 Regarding the 2180 cm -1 peak there is no doubt about the origin of this peak to C≡N modes, which was confirmed by 15 10 observed a peak at 3362 cm -1 in the 3200-3600 cm -1 region and attributed it to stretching modes of N-H bonds in NH and NH 2 configurations and to hydroxyl group OH which can be incorporated after exposing the films to air. The presence of the CH x band and the N-H and OH band means the contamination of hydrogen and oxygen in the films, no clear dependence on the ion energy and R(I/A) being observed.…”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…It is known that all the features in the 1000-1700 cm -1 region in carbon samples are due to skeletal C=C vibrations and this suggests that the 1000-1700 cm -1 band in this study is attributed to C=C modes or mixed C=N modes. 2,9 Regarding the 2180 cm -1 peak there is no doubt about the origin of this peak to C≡N modes, which was confirmed by 15 10 observed a peak at 3362 cm -1 in the 3200-3600 cm -1 region and attributed it to stretching modes of N-H bonds in NH and NH 2 configurations and to hydroxyl group OH which can be incorporated after exposing the films to air. The presence of the CH x band and the N-H and OH band means the contamination of hydrogen and oxygen in the films, no clear dependence on the ion energy and R(I/A) being observed.…”
Section: Resultssupporting
confidence: 48%
“…[6][7][8][9][10] The ion beam assisted deposition (IBAD) technique is vacuum deposition of material onto a substrate combined with simultaneous ion irradiation. 3,7 The flux and the energy of incident ions can be changed independently of the flux of depositing atoms, thereby easily controlling the chemical composition of compound films.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Also, CN X films have been reported to absorb water, as determined by the IR absorption in the range of the OH stretching mode around 3500 cm Ϫ1 . 23 Absorption by as much as 5 wt.% has been observed by weight increase measurements. 26 Absorption of water vapor is a reasonable explanation for the increase of over time, since the magnitude of the change shows a strong correlation with the degree of porosity in the films (c.f.…”
mentioning
confidence: 91%
“…This has to be explained by diffusion, presumably of water vapor, into the structure. 17,23 A corresponding change of the electric resistance of carbon films under exposure to air, due to the adsorption of water vapor, has been reported in the literature. 24,25 Also, CN X films have been reported to absorb water, as determined by the IR absorption in the range of the OH stretching mode around 3500 cm Ϫ1 .…”
mentioning
confidence: 95%
“…Currently, researchers have found that surface with hydrophobic behaviour shows great potential in various applications such as cosmetics, bio-medical, plating, painting and printing, semiconductors, as well as hard disk drives [6][7][8][9][10]. Since then, many attempts to grow thin films with hydrophobic behaviour were carried out using a variety of techniques such as dielectric barrier discharge (DBD) [11][12][13], sputtering [14], ion beam deposition [15], pulse laser deposition [16] and radio frequency plasma enhanced chemical vapour deposition (rf-PECVD) [9]. Hydrophobicity is generally attributed by many factors such as surface roughness, morphology and chemical bonding [17].…”
Section: Introductionmentioning
confidence: 99%